Secreted peptidases contribute to virulence of fish pathogen Flavobacterium columnare - Thunes, Nicole C.; Mohammed, Haitham H.; Evenhuis, Jason P.; Lipscomb, Ryan S.; Pérez-Pascual, David; Stevick, Rebecca J.; Birkett, Clayton; Conrad, Rachel A.; Ghigo, Jean-Marc; McBride, Mark J. (Frontiers in Cellular and Infection Microbiology, 2023)
Flavobacterium columnare causes columnaris disease in freshwater fish in both natural and aquaculture settings. This disease is often lethal, especially when fish population density is high, and control options such as vaccines are limited. The type IX secretion system (T9SS) is required for F. columnare virulence, but secreted virulence factors have not been fully identified. Many T9SS-secreted proteins are predicted peptidases, and peptidases are common virulence factors of other pathogens. T9SS-deficient mutants, such as ΔgldN and ΔporV, exhibit strong defects in secreted proteolytic activity. The F. columnare genome has many peptidase-encoding genes that may be involved in nutrient acquisition and/or virulence. Mutants lacking individual peptidase-encoding genes, or lacking up to ten peptidase-encoding genes, were constructed and examined for extracellular proteolytic activity, for growth defects, and for virulence in zebrafish and rainbow trout. Most of the mutants retained virulence, but a mutant lacking 10 peptidases, and a mutant lacking the single peptidase TspA exhibited decreased virulence in rainbow trout fry, suggesting that peptidases contribute to F. columnare virulence.